Arabinogalactan Proteins in Plant Roots – An Update on Possible Functions - Hromadová, Dagmar; Soukup, Aleš; Tylová, Edita (Frontiers in Plant Science, 2021)
Responsiveness to environmental conditions and developmental plasticity of root systems are crucial determinants of plant fitness. These processes are interconnected at a cellular level with cell wall properties and cell surface signaling, which involve arabinogalactan proteins (AGPs) as essential components. AGPs are cell-wall localized glycoproteins, often GPI-anchored, which participate in root functions at many levels. They are involved in cell expansion and differentiation, regulation of root growth, interactions with other organisms, and environmental response. Due to the complexity of cell wall functional and regulatory networks, and despite the large amount of experimental data, the exact molecular mechanisms of AGP-action are still largely unknown. This dynamically evolving field of root biology is summarized in the present review.